PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR PEMBIAYAAN YANG TERDAFTAR DI BEI TAHUN 2014-2018 - Ayu Lestari; Pudyartono Pudyartono; Fatichatur Rachmaniyah (J-MACC, 2020)
Profit growth is one indicator that is used to measure the achievement of the company in a period. Profit growth can be predicted through financial ratios analysis. This study aims to determine the effect of financial ratios on profit growth in finance sector companies listed on the IDX in 2014-2018. This study uses a quantitative approach. The sampling technique is through a purposive sampling method with a population of the total number of finance sector companies listed on the IDX in 2014-2018. While the data analysis technique uses multiple linear regression analysis. The results showed that a partial current ratio, debt to asset ratio, and return on asset had a positive and significant impact on profit growth. Return on equity affects negative and not significant to profit growth. Simultaneously, the financial ratios (current ratio, debt to asset ratio, return on asset, and return on equity) have a significant effect on the growth.